2005
DOI: 10.1542/peds.2005-0607
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national Study of Fighting and Weapon Carrying as Determinants of Adolescent Injury

Abstract: ABSTRACT. Objectives. We sought to (1) compare estimates of the prevalence of fighting and weapon carrying among adolescent boys and girls in North American and European countries and (2) assess in adolescents from a subgroup of these countries comparative rates of weapon carrying and characteristics of fighting and injury outcomes, with a determination of the association between these indicators of violence and the occurrence of medically treated injury.Design and Setting. Cross-sectional self-report surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
129
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(154 citation statements)
references
References 42 publications
16
129
3
4
Order By: Relevance
“…The majority of countries reporting the highest prevalence of physical fighting by boys were from Eastern or Central Europe. 34 Our estimates from Chile appear to be within the usual range of prevalence that has been reported elsewhere.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The majority of countries reporting the highest prevalence of physical fighting by boys were from Eastern or Central Europe. 34 Our estimates from Chile appear to be within the usual range of prevalence that has been reported elsewhere.…”
Section: Discussionsupporting
confidence: 85%
“…In a study involving 37,571 11-15-years-old in-school adolescents conducted in 2001/2002 in 9 different countries, Pickett reported that the prevalence of boys involved in physical fighting during the previous year ranged from 37% in Finland to 69% in the Czech Republic. 34 The overall average prevalence was 58%. Among girls, the prevalence of physical fighting was much lower ranging from 13% in Finland to 32% in Hungary and an overall average of 24%.…”
Section: Discussionmentioning
confidence: 97%
“…Neste estudo, ser do sexo masculino aumenta o risco para ambos os desfechos estudados, assim como em todos os demais artigos que investigaram a questão de gênero 16,17,18,19,20,21,22,23,24,25 . Os achados sugerem que meninos são os que mais usam a violência para resolver seus conflitos interpessoais.…”
Section: Discussionunclassified
“…In addition to males more likely to carry handgun than females (Pickett et al, 2005), research has identified racial and ethnic differences. Studies in the U.S. indicate that African-Americans and Latinos are more likely to carry weapons such as handguns compared to Whites and Asians (e.g., Craun & Detar, 2015;Durant, Krowchuk, Kreiter, Sinal, & Woods 1999;Spano, 2012) in part because of more extensive and greater duration of involvement in criminal violence (Bierie, 2014;Craun & Deter, 2015;Doherty & Ensminger, 2014).…”
Section: Introductionmentioning
confidence: 99%